Feasibility Evaluation of a 110 cc-Class Automatic Motorcycle Engine Cutaway for Supporting Practical Curriculum Implementation in Automotive Vocational Education - Ichsan Nasution; Hasan Maksum; Waskito Waskito; Dwi Rangga Ariga (AEEJ : Journal of Automotive Engineering and Vocational Education, 2026)
Automatic motorcycle engines are closed mechanical assemblies that limit students’ observation of internal components during vocational practice. This study developed and evaluated the feasibility of a 110 cc-class automatic motorcycle engine cutaway for supporting practical curriculum implementation in automotive vocational education. A Research and Development design with the ADDIE model was used. The product exposed key components, including the piston, cylinder, combustion chamber, crankshaft, valve mechanism, lubrication passages, and automatic transmission section, as a real-object medium for observing automatic engine mechanisms. Feasibility data were obtained from two media experts, two material experts, and responses from 25 Automotive Engineering students after limited implementation. Five-point Likert-scale data were analyzed descriptively. Media expert validation reached 86%, and material expert validation reached 90%, both categorized as highly feasible. Student responses reached 90%, categorized as very good. The cutaway was feasible and accepted, although learning effectiveness was not measured.